Enabling circular economy dynamics in the plastics and steel industries: Perspectives from multiple stakeholders - Sun Xi; Sophie M. Behr; Merve Kücük (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
This paper investigates the perspectives of stakeholder groups in the plastic and steel value chains on transitioning toward a circular economy (CE). Through semistructured interviews with 31 business stakeholders, we analyze business strategies, key factors, challenges and opportunities, as well as coordination and regulatory needs for a successful industry-wide CE transition. Our findings highlight the effectiveness of CE regulations in driving CE-oriented business strategies and fostering coordination within fragmented value chains. While stakeholders acknowledge the significance of product design and the crucial role of producers, differing opinions emerge on the role and adequacy of regulations. This nuanced understanding contributes to an evidencebased analysis of the distinct incentives that shape the transitional activities in these industries.
Keywords: D83; L61; 65; Q58; 330; stakeholder interview; circular transition; value chain; plastics; steel